Evaluasi Pelaksanaan Tugas Guru Kelas Inklusi di SD Penyelenggara Pendidikan Inklusif Kota Surabaya - Odas Odas (Universitas Negeri Padang, 2023)
This study aims to assess the performance of duties of classroom teachers in inclusive schools based on a general guideline implementation of inclusive education in 2011.The approach in this research is descriptive quantitative evaluation methods. Samples were taken based on the representation and the division of the city of Surabaya covering 5 areas including Surabaya region north, south, central, east and west. Each region is represented 2 schools and each school selected third grade teacher at random. The results showed that (1) the class teachers make an effort to create a conducive learning climate by 78% are very good, appropriate evaluation results, (2) classroom teachers prepare and implement academic and non-academic assessment by 49% including the unfavorable category, evaluation results do not match, (3) prepare classroom teachers PPI together with GPK by 43% including the unfavorable category, the results of the evaluation are not appropriate, (4) classroom teachers implement learning activities, assessment, and follow-up of 63% are good , corresponding evaluation results, (5) classroom teachers provide remedial learning programs and enrichment / acceleration by 63%, including both categories, the results of appropriate evaluation, (6) the administration of the class teacher grade of 83% are very good, and the corresponding evaluation results (7) classroom teachers develop programs and implement practical guidance for all students by 63%, including both categories, the results of the evaluation accordinglyÂ